Sexually Transmitted Infections among Key Populations in India: Systematic Review with Spatiotemporal Distribution - Bhatta, Mihir; Venkatesh, Bhumika Tumkur; Ghosh, Utsha; Aridoss, Santhakumar; Biswas, Subrata; Banerjee, Papiya; Ghosh, Piyali; Khan, Pankaj; Royal, Abhishek; Das, Nibedita; et al. (Archives of Clinical and Biomedical Research, 2025)
In the developing world, sexually transmitted infections (STIs) are among the key sources of health and financial adversities, contributing significantly to morbidity, death, and stigma. Goal of the current systematic review is to identify the geographic distribution and current of STIs among the Indian key population. A protocol was prepared and registered in the PROSPERO, with the registration number CRD42022357425 and published as a Systematic Review Protocol. The data on frequency and prevalence of four treatable STIs— syphilis, chlamydia, gonorrhea and trichomoniasis, focused on the MSM (men sex with men) and FSW (female sex workers) populations, followed by H/TG (Hijras with Transgenders) and PWID (those who inject drugs), was gathered and analyzed from different geographical regions in India. However, it was found that most of the research used aetiological diagnosis to report prevalence and were belongs to the western and southern regions of India. Few studies from the northern and north eastern regions were also being found. In the light of present findings and with the identified limitations, it can be concluded that existing HIV surveillance system under NACP (National AIDS Control Programme) in India, can be utilized with additional bio-specimen collection to determine STI prevalence among high risk populations.